Hole transport material and solar battery using the same
A D-A-D structured hole transport material with a fluorene ring and electron-donating groups addresses the inefficiencies of existing materials by improving mobility and solubility, enhancing solar cell performance and durability while reducing production costs.
Patent Information
- Application Number
- JP2023096126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing hole transport materials for perovskite solar cells face challenges such as high cost, low mobility, stability issues, and inefficiency due to the need for dopants like cobalt complexes, and they exhibit reduced performance over time due to lithium ion diffusion and hygroscopicity.
A hole transport material with a D-A-D structure, featuring a fluorene ring in the A part and electron-donating groups at the 2nd and 7th positions, which improves electron-withdrawing properties and reduces steric interference, allowing for efficient hole transport and increased solubility, and can be synthesized using inexpensive materials with fewer steps.
The material enhances hole transport efficiency, improves solar cell performance, reduces light absorption loss, and increases durability by minimizing steric interference and using non-hygroscopic additives, leading to higher photoelectric conversion efficiency and lower production costs.
Smart Images

Figure 2024177790000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hole transport material and a solar cell using the hole transport material. [Background technology]
[0002] Solar cells generally use elements such as silicon, compound semiconductors, and organic semiconductors, but hybrid solar cells (perovskite solar cells) are attracting attention because of their high light-collecting ability as well as the possibility of making them thin films and reducing costs.
[0003] Non-Patent Document 1 discloses a perovskite solar cell comprising a glass substrate with a transparent conductive film, a blocking layer consisting of a dense titanium dioxide (TiO2) film, a power generation layer formed by laminating lead bromide (PbBr2), lead iodide (PbI2), methylamine hydrobromide (CH5N·HBr: hereinafter sometimes abbreviated as "MABr"), and formamidine hydroiodide (CH4N2·HI: hereinafter sometimes abbreviated as "FAI") as perovskite compounds that are excited by light to generate electrons, on porous titanium dioxide (TiO2), a hole transport layer, and electrodes.
[0004] The power generation layer is a mixed halide (FAPbI3) 0.85 (MAPbBr3) 0.15 It is formed as a perovskite layer.
[0005] Conventionally, 2,2',7,7'-tetrakis(N,N'-di-p-methoxyphenylamine)-9,9'-spirobifluorene (commonly called "spiro-OMeTAD"; hereafter, this name will be used) represented by the following general formula (A) has been widely used as the hole transport material for the hole transport layer. When crystals of a perovskite compound absorb light, electrons and holes are generated. The holes are transported to the counter electrode by the hole transport material, and the electrons move to the photoelectrode, and this cycle is repeated to generate electricity.
[0006] [ka]
[0007] Although spiro-OMeTAD is commercially available and easily available, as reported in Non-Patent Document 1, spiro-OMeTAD has a problem that it is essentially difficult to reduce the cost because it requires many synthesis and purification steps. In addition, there are problems such as a relatively low hole mobility and the need for a dopant such as a cobalt complex to function efficiently and stably as a hole transport material. In addition, when spiro-OMeTAD is incorporated into a solar cell as a hole transport material, it can exhibit high initial performance, but there is a problem with the sustainability of the performance. Therefore, research is being conducted on hole transport materials that can be provided at low cost and have an efficient and stable hole transport effect.
[0008] In this regard, Non-Patent Document 1 reports a compound called LD29, which has a carbazole ring in the acceptor (hereinafter referred to as "A") portion and a triphenyldimethoxyamino group in the donor (hereinafter referred to as "D") portion, and is represented by the following general formula (B) in which these are linked to a donor-acceptor-donor type (hereinafter referred to as "DAD type") structure, as a new hole transport material. In a solar cell using such LD29 as a hole transport material, the conversion efficiency was 14.29% without dopant, but the addition of lithium bis(trifluoromethanesulfonyl)imide (hereinafter sometimes referred to as "LiTFSI"), 4-tert-butylpyridine (TBP), and a cobalt complex (FK209) as dopants improved the conversion efficiency to 18.0%, achieving a conversion efficiency comparable to that of spiro-OMeTAD.
[0009] [ka]
[0010] In LD29, a carbazole ring is introduced into the A portion, but it is thought that the lone pair of electrons on the heteroatom (nitrogen atom) at the 9th position of the carbazole ring acts in a direction that inhibits electron withdrawal. This reduces the hole transport ability in the LD29 molecule, and it is assumed that it is difficult to obtain sufficient solar cell efficiency in solar cells that use LD29 as a hole transport material. In addition, the solar cell has a problem in terms of durability, such as a decrease in solar cell efficiency over time. This is thought to be due to the lithium ions contained in LiTFSI, which is added as a dopant to the hole transport material, diffusing out of the hole transport layer and the strong hygroscopicity of LiTFSI itself.
[0011] In addition, Non-Patent Document 2 reports a compound called YN1 represented by the following general formula (C), and Non-Patent Document 3 reports a compound called PTZ2 represented by the following general formula (D). Both compounds have a DAD type structure, but have the same problems as LD29 described above.
[0012] [ka]
[0013] [ka]
[0014] Thus, much research is being conducted on low molecular weight organic materials such as hole transport materials having a DAD structure. The inventors of the present application also reported in Patent Document 1 a low molecular weight organic material called DHCF-3, which is represented by the following general formula (E). It has been confirmed that such DHCF-3 stably exhibits excellent hole transport properties and functions well as a hole transport material, and when introduced into a solar cell, it exhibits good solar cell performance. Here, DHCF-3 has a fluorene ring in the A portion, a 4-(bis(4-methoxyphenyl)amino)phenyl group in the D portion, and has a structure in which the same substituent as in the D portion is introduced to the carbon at the 9th position of the fluorene ring in the A portion via a CC double bond.
[0015] [ka]
[0016] However, in the hole transport material described in Patent Document 1, the substituent of the A portion is bulky, so that the D portion on one side and the A portion are arranged sterically close to each other, and the D portion on the adjacent side is arranged more twisted relative to the fluorene ring of the A portion, which is assumed to weaken the π conjugation and inhibit the hole transport effect. [Prior art documents] [Patent documents]
[0017] [Patent Document 1] Patent Publication No. 2023-46046 [Non-patent literature]
[0018] [Non-Patent Document 1] Xuepeng Liu et al., “A star-shaped carbazole-based hole-transporting material with triphenylamine side arms for perovskite solar cells,” J.Mater.Chem.C., 2018, 6, 12912-12918 (DOI:10.1039 / c8tc04191a) [Non-Patent Document 2] Peng Xu et al., “DAD-Typed Hole Transport Materials for Efficient Perovskite Solar Cells: Tuning Photovoltaic Properties via the Acceptor Group”, ACS Appl. Mater. Interfaces 2018, 10, 23 (DOI:10.1021 / acsami.8b04003) [Non-Patent Document 3] Roberto Grisorio et al., “Molecular Tailoring of Phenothiazine-Based Hole-Transporting Materials for High-Performing Perovskite Solar Cells,” ACS Energy Lett. 2017, 2, 5, 1029-1034 (DOI:10.21 / acsenergylett.7b00054) Summary of the Invention [Problem to be solved by the invention]
[0019] In view of the above problems of the conventional technology, there is still a need to provide a hole transport material that stably exhibits excellent hole transport properties. There is also a need to provide a hole transport material at low cost. There is also a need to provide a solar cell with high cell performance at low cost. [Means for solving the problem]
[0020] The hole transport material according to the present invention has the following characteristic features: A hole transport material having a donor-acceptor-donor (DAD) structure represented by the following general formula (1): [ka] [In general formula (1), The two D regions are regions having the same structure, Each D moiety has a structure selected from the following groups (I), (II), (III), (IV), and (V): [ka] (In group (I), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 , R 2a2 , R 2b1 , and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H and R 2b1 and R 2b2 At least one of them is -H.) [ka] (In group (II), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 and R 2a2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H, R 4 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; Y is 1 or 2, and R 5 If exists, R 5 is introduced at the 3- or 4-position of the thiophene ring in group (II), -H and -C n H 2n+1 where n is an integer of 1 to 8. [ka] [ka] [ka] (In group (III), group (IV), and group (V), X and Y are each independently an integer of 0, 1, or 2; The Two R's D each independently has a structure represented by the following group (I'), [ka] (In the group (I´), X' and Y' are each independently an integer of 0, 1, or 2. R 1 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 ´ and R 3 ´ is not simultaneously -H, R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 ´ and R 2a2 ´ is at least one of -H and R 2b1 ´ and R 2b2 ´ At least one of them is -H. )) In general formula (1), R A has a structure represented by the following group (VI): [ka] (In group (VI), R 6 -C m H 2m+1 where m is an integer between 6 and 16.)
[0021] According to the above-mentioned configuration, it is possible to provide a hole transport material having excellent hole transport properties capable of stably and efficiently capturing and transporting holes. In detail, the hole transport material of this configuration has a DAD type structure, and the A part is configured to include an electron-accepting group such as a fluorene ring composed of carbon atoms and hydrogen atoms, and the D part is introduced to the 2-position and the 7-position on the fluorene ring, respectively, and further, the 5-alkyl-2-thienyl group is introduced to the 9-position on the fluorene ring via a carbon-carbon double bond. By configuring in this way, the electron-withdrawing property of the A part is improved, and the steric interference between the substituent of the A part and the D part, which was a technical problem in the past, is eliminated, so that the push-pull effect in the molecule of the hole transport material is increased, and the charge transfer property in the molecule is improved. As a result, the transfer of electrons in the molecule is smooth, and the charge separation of HOMO-LUMO becomes clearer. That is, in the hole transport material having the above configuration, electrons are concentrated in the D portion at the HOMO and HOMO-1 levels, and electrons are concentrated in the A portion at the LUMO level. Thus, the hole transport material having this configuration can exhibit excellent hole transport properties due to improved charge transfer properties within the molecule. Furthermore, by using a fluorene ring that does not contain a heteroatom in the A portion, the inhibition of electron-withdrawing properties caused by the lone pair of heteroatoms that occurs in LD29 and the like described in the [Prior Art] section is eliminated, and the material can function more effectively as a hole transport material.
[0022] In addition, since the hole transport material of the present configuration has a deep HOMO energy level, the arrangement with the HOMO level of the perovskite can be appropriately adjusted, which has the advantage that the hole transport properties can be improved and the solar cell efficiency can be easily improved.
[0023] The hole transport material of this configuration shows almost no light absorption in the visible light region of 500 nm or more, and its light absorption intensity in the 400-500 nm region is as weak as that of the conventionally widely used spiro-OMeTAD. Therefore, a solar cell using the hole transport material of this configuration can minimize the light absorption loss caused by the hole transport material, and is expected to have high photoelectric conversion efficiency.
[0024] The hole transport material of this configuration also has excellent properties in terms of solubility in a solvent. In particular, the solubility in a solvent is improved by introducing a 5-alkyl-2-thienyl group having a long-chain alkyl group to the fluorene ring of the A portion. Therefore, the workability in manufacturing a solar cell is improved, and wet processes such as a coating method by spin coating can also be used, making it easy to form a hole transport layer of a solar cell. In addition, since the hole transport material of this configuration is soluble in a non-polar solvent, it is possible to manufacture a hole transport layer of a solar cell using a solvent that is inexpensive and has a low environmental impact. On the other hand, when manufacturing a hole transport layer, spiro-OMeTAD, which has been widely used in the past, generally uses chlorobenzene as a solvent. However, chlorobenzene contains chlorine atoms in the molecule and is expensive, so that the cost of equipment including post-processing such as solvent disposal is high, and there are problems such as a large load on safety and the environment due to exhaust leakage.
[0025] In addition, the hole transport material of the present invention can be synthesized in a short time with few synthesis steps using inexpensive raw materials, and a high purity product can be provided through a simple purification step. Therefore, it is possible to reduce the costs required for synthesis and purification without requiring expensive reagents or complicated steps, and it is possible to provide an inexpensive, high-performance hole transport material.
[0026] Furthermore, the hydrophobic effect of the long-chain alkyl group of the 5-alkyl-2-thienyl group introduced into the A portion can improve the water resistance of a solar cell incorporating the hole transport material of this configuration. In addition, the hole transport material according to this embodiment allows smooth intramolecular and intermolecular hole movement, suppressing oxidation of the molecules and improving durability. This is expected to improve the durability of solar cells.
[0027] As described above, the hole transport material of the present invention has excellent properties and can be suitably used as a hole transport material for solar cells. When the hole transport material of the present invention is used in a hole transport layer of a perovskite solar cell or the like, the cell exhibits excellent performance in initial experiments. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is a schematic cross-sectional view of a perovskite solar cell. [Diagram 2] FIG. 1 is a top perspective view of a perovskite solar cell. [Diagram 3] FIG. 1 is an explanatory diagram of power generation in a perovskite solar cell. [Figure 4] FIG. 1 is an explanatory diagram showing a procedure for producing a perovskite solar cell. [Diagram 5] FIG. 2 shows a synthesis scheme of the hole transport material (DHCF-17) prepared in Example 1. [Figure 6] FIG. 2 shows the results of 1H NMR analysis confirming the synthesis of the hole transport material (DHCF-17) prepared in Example 1. [Figure 7] FIG. 2 shows the results of mass spectrometry confirming the synthesis of the hole transport material (DHCF-17) prepared in Example 1. [Figure 8] FIG. 2 shows the results of ultraviolet-visible-near infrared spectroscopic analysis confirming the synthesis of the hole transport material (DHCF-17) prepared in Example 1. [Figure 9] 1 is a graph showing the results of cell performance evaluation of the solar cells investigated in Example 3, showing the IV characteristics of each solar cell investigated. [Figure 10] 1 is a graph showing an example of the results of the cell performance evaluation of the solar cells investigated in Example 4, showing the IV characteristics of each solar cell investigated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] An embodiment of a perovskite solar cell 10 (one example of a solar cell 10; hereinafter, referred to as "solar cell 10") using a hole transport material according to the present invention will be described below with reference to the drawings. In this embodiment, as one example of a solar cell 10, a solar cell 10 configured with a perovskite layer 44 made of an organic and inorganic hybrid compound will be described. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the present invention.
[0030] (Basic configuration of solar cell 10 according to this embodiment) As shown in FIG. 1 and FIG. 2, the solar cell 10 according to the present embodiment includes a substrate 2 having a transparent substrate 21 and a transparent conductive film 22, a blocking layer 3 provided on the substrate 2, which transfers electrons to the transparent conductive film 22 and separates the hole transport layer 5 and the transparent conductive film 22 to prevent recombination of electrons and holes (reverse electron transfer), a power generation layer 4 provided on the blocking layer 3 and formed by laminating a perovskite layer 44 excited by light to generate electrons on a porous semiconductor 41, and a hole transport layer 5 provided on the power generation layer 4 through which holes generated in the perovskite layer 44 pass. The solar cell 10 also includes an electrode 6 provided on the surface of the blocking layer 3 and composed of a photoelectrode 61 that emits electrons through the transparent conductive film 22 and a counter electrode 62 that is provided on the surface of the hole transport layer 5 and receives electrons. The arrangement of the electrode 6 is not particularly limited as long as it is possible to transfer electrons, for example, by connecting the photoelectrode 61 to the transparent conductive film 22 with a conductor. In order to increase the durability of the solar cell 10, the counter electrode 62 may be protected by a transparent substrate 21 or the like.
[0031] The transparent substrate 21 is made of a material having optical transparency. For example, a transparent glass substrate, a frosted semi-transparent glass substrate, a transparent resin substrate, etc. can be used. For the transparent conductive film 22, for example, fluorine-doped tin oxide (FTO), tin oxide (TO), tin-doped indium oxide (ITO), zinc oxide (ZnO), aluminum-doped zinc oxide (AZO), etc. can be used.
[0032] The blocking layer 3 and the porous semiconductor 41 are preferably made of a metal oxide, such as titanium dioxide (TiO2), zinc oxide (ZnO), niobium oxide (Nb2O5), tin dioxide (SnO2), or aluminum oxide (Al2O3). In particular, it is preferable to configure the blocking layer 3 as a sintered body of titanium dioxide (TiO2), which can secure a large surface area for stacking the perovskite layer 44. In addition, the blocking layer 3 is formed so that a part of it extends into the transparent conductive film 22, and the transparent conductive film 22 is partitioned. Furthermore, the blocking layer 3 forms a dense insulating layer 31 so that electrons can pass through in the stacking direction but are difficult to move in the lateral direction. In other words, electrons that have entered from the blocking layer 3 move smoothly in the stacking direction of the transparent conductive film 22 and are supplied to the photoelectrode 61, and the insulating layer 31 prevents the electrons from moving to the counter electrode 62, so that no short circuit occurs.
[0033] The perovskite layer 44 is produced by reacting a compound (PbX2, X = halogen element) composed of lead and halogen element X with methylammonium iodide (CH3NH3I: hereinafter sometimes abbreviated as "MAI"). Specifically, a solution 42 containing lead and halogen element X is infiltrated into the inside of the pores of a porous semiconductor 41, dried, and then immersed in a mixed solution 43 of MAI, and crystals of a perovskite compound (CH3NH3PbI3 when X = I) that forms the perovskite layer 44 are rapidly produced. Note that although iodine, bromine, chlorine, etc. can be used as the halogen element X, it is preferable to use iodine, which has high morphological stability. In addition, a mixed cation-mixed halide ((FAPbI3)) using MABr and 0.2M lead bromide (PbBr2), FAI and lead iodide (PbI2) was also used. 1-x (MAPbBr3) x) can also be used. For example, (FAPbI3) 0.85 (MAPbBr3) 0.15 etc. can be suitably used.
[0034] A hole transport material described later is used for the hole transport layer 5. For the electrode 6, for example, a simple metal or alloy of a metal such as gold, platinum, silver, or copper, or an oxide conductor such as fluorine-doped tin oxide (FTO) or tin-doped indium oxide (ITO) can be used.
[0035] Here, the principle of how the solar cell 10 generates electricity will be described with reference to Fig. 3. When light such as sunlight or indoor light is incident on the transparent substrate 21, this incident light is hardly absorbed and passes through the substrate 2 and the blocking layer 3, and most of it reaches the power generation layer 4. When the incident light that has reached the power generation layer 4 is irradiated onto the perovskite layer 44, the perovskite layer 44 absorbs the light energy and becomes excited. When the energy level of the perovskite layer 44 becomes higher than the conduction band potential of the metal oxide that is the porous semiconductor 41 by a predetermined level or more due to this excitation, electrons are injected from the perovskite layer 44 into the porous semiconductor 41. The injected electrons pass through the blocking layer 3 and are collected by the photoelectrode 61.
[0036] On the other hand, holes generated in the perovskite layer 44 reach the counter electrode 62 via the hole transport layer 5, where they recombine with electrons that have passed through the external load 7. In other words, a potential gradient is generated between the photoelectrode 61 and the counter electrode 62, so that power can be supplied by connecting the external load 7 between the two electrodes.
[0037] (Procedure for producing solar cell 10 according to this embodiment) The procedure for producing the solar cell 10 according to this embodiment will be described with reference to FIG. 4. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the invention. The solar cell 10 can be produced with reference to known techniques such as those described in Michael Saliba et al., “Correction to “How to Make over 20% Efficient Perovskite Solar Cells in Regular (nip) and Inverted (pin) Architectures”, Chem. Mater., 2018, 30, 4193-4218.
[0038] First, the transparent conductive film 22 is formed on the transparent substrate 21 to prepare the substrate 2. The transparent conductive film 22 is laminated on the transparent substrate 21 by, for example, CVD (chemical vapor deposition) or sputtering. Next, the transparent conductive film 22 is partially removed by laser scribing to form a recess 221 for the insulating layer 31, and then washed. Next, the blocking layer 3 is formed on the entire surface of the substrate 2 by ALD (atomic layer deposition) or SPD (spray pyrolysis). The blocking layer 3 is preferably formed as a TiO2 dense layer. Next, a porous semiconductor 41, which is a nanoparticle sintered layer, is formed near the center on the masked substrate 2 and blocking layer 3. It is preferably formed as a TiO2 porous layer (p-TiO2). This porous semiconductor 41 is formed by diluting a nanoparticle paste with a solvent, applying and drying, for example, by spin coating at a rotation speed of 4000 rpm to 6000 rpm, and then removing the mask and heating at 450°C to 550°C to form a sintered layer.
[0039] For example, a solution 42 of PbI2 in N,N-dimethylformamide is prepared and dropped onto the porous semiconductor 41, after which the solution is permeated into the pores (p-TiO2) and excess solution is removed by spin coating at a rotation speed of, for example, 5000 rpm to 8000 rpm. The solution is then dried at 60°C to 120°C (preferably 70°C to 90°C) to form a PbI2 layer.
[0040] The porous semiconductor 41, in which the substrate 2, blocking layer 3, and lead iodide have been infiltrated, is immersed in an isopropyl alcohol solution 43 (2-20 mg / ml) of MAI (CH3NH3I) at 0°C to 80°C (preferably at room temperature) (MAI immersion method). PbI2 and MAI react to form a perovskite compound [(CH3NH3)PbI3(MAPbI3)] as a perovskite layer 44 inside and on the top of the pores of the porous semiconductor 41, and then the porous semiconductor 41 is flooded with a pure isopropyl alcohol solution and dried at 60°C to 120°C (preferably 70°C to 100°C). The mixed cation-mixed halide ((FAPbI3) 1-x (MAPbBr3) x ) type perovskite compounds can be prepared in a similar manner.
[0041] The hole transport material according to the present embodiment is prepared as, for example, a chlorobenzene solution of 60 to 90 mg / ml. The solution is dropped onto the perovskite layer 44, and excess solution is removed by spin coating, followed by drying to form the hole transport layer 5. The hole transport material may contain an additive such as 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (hereinafter, sometimes referred to as "TPFB"). When TPFB is added, the TPFB is preferably 0.01% by weight to 100% by weight of the hole transport material, and particularly preferably 0.1% by weight to 50% by weight. For example, the hole transport material according to the present embodiment is weighed out to be 30 mM, and TPFB equivalent to 10% by weight is added thereto, and the resulting solution is dissolved in chlorobenzene to form the hole transport layer 5.
[0042] The steps from forming the PbI2 layer to forming the hole transport layer 5 are preferably carried out in a dry nitrogen atmosphere such as in a glove box. Finally, a thin film of gold or the like is attached to the surfaces of the blocking layer 3 and the hole transport layer 5 by a method such as vacuum deposition to form an electrode 6.
[0043] In the above-mentioned manufacturing procedure, the crystal growth of the perovskite compound forming the perovskite layer 44 is controlled in two steps, but this may be performed in one step. For example, a perovskite ((CH3NH3)PbI3) solution is permeated into the pores of the porous semiconductor 41 by spin coating. Toluene is dropped during spinning to precipitate microcrystals and make the surface mirror-finished (poor solvent precipitation method). Then, the hole transport layer 5 may be formed from the hole transport material according to this embodiment.
[0044] (Hole Transport Material According to the Present Embodiment) The hole transport material according to this embodiment has a DAD structure, and a suitable example thereof is a compound represented by the following general formula (1):
[0045] [ka]
[0046] An electron-accepting group (electron-withdrawing group) is introduced into the A portion, and here, the A portion is configured as a fluorene ring, and a substituent R A is introduced. The fluorene ring is composed of carbon atoms and hydrogen atoms, and does not contain heteroatoms such as nitrogen atoms. Furthermore, the fluorene ring is linked to the D moieties at the 2-position and 7-position, respectively. The D moieties linked to the 2-position and 7-position on the fluorene ring are preferably configured as the same group.
[0047] The D portion is constituted as an electron-donating group, and preferably has one structure selected from the following group (I), group (II), group (III), group (IV), or group (V). The wavy line in the group indicates the bonding position with the A portion.
[0048] [ka]
[0049] [ka]
[0050] [ka]
[0051] [ka]
[0052] [ka]
[0053] In the groups (I), (II), (III), (IV), and (V), X and Y are independently an integer of 0, 1, or 2. Accordingly, the groups (I) and (II) each include a diphenylamino group (X=0, Y=0), a 4-(diphenylamino)phenyl group (X=1, Y=0), a 4'-(diphenylamino)[1,1'-biphenyl]-4-yl group (X=2, Y=0), a 5-(diphenylamino)thiophen-2-yl group (X=0, Y=1), a 5'-(diphenylamino)[2,2'-bithiophene]-5-yl group (X=0, Y=2), a 5-[4-(diphenylamino)phenyl group (X=0, Y=0 ... and 5-[4'-(diphenylamino)[1,1'-biphenyl]-4-yl]thiophen-2-yl group (X=1, Y=1), 5-[4'-(diphenylamino)phenyl][2,2'-bithiophene]-5-yl group (X=1, Y=2), and 5'-[4'-(diphenylamino)[1,1'-biphenyl]-4-yl][2,2'-bithiophene]-5-yl group (X=2, Y=2).
[0054] In groups (I) and (II), each substituent is independently selected; R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; and R 1 and R 3 may be the same or different, but cannot be simultaneously -H. Therefore, R 1 and R 3 teeth 、 At least one of them is -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 is selected from.
[0055] R 1 and R 3 -C in n H 2n+1is an alkyl group, whether linear or branched. There is no particular restriction on the chain length as long as n is within the range of 1 to 8. Specifically, the alkyl group may be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, an t-butyl group, an n-pentyl group, an isopentyl group, an neopentyl group, an t-pentyl group, an s-pentyl group, a 2-methylbutyl group, a 1-ethylpropyl group, a 2-ethylpropyl group, an n-hexyl group, an isohexyl group, an neohexyl group, an t-hexyl group, a 2,2-dimethylbutyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1-ethylbutyl group, a 2-ethylbutyl group, a 1-propylpropyl group, an n-heptyl group, an isoheptyl group, an s-heptyl group, an t-heptyl group, a 2,2-dimethylpentyl group, a 3,3-dimethylpentyl group, a 1-methylhexyl group, a 2 Examples of the alkyl groups include 1-methylhexyl group, 3-methylhexyl group, 4-methylhexyl group, 1-ethylpentyl group, 2-ethylpentyl group, 3-ethylpentyl group, 1-propylbutyl group, 2-propylbutyl group, n-octyl group, isooctyl group, t-octyl group, neooctyl group, 2,2-dimethylhexyl group, 3,3-dimethylhexyl group, 4,4-dimethylhexyl group, 1-methylheptyl group, 2-methylheptyl group, 3-methylheptyl group, 4-methylheptyl group, 5-methylheptyl group, 1-ethylhexyl group, 2-ethylhexyl group, 3-ethylhexyl group, 4-ethylhexyl group, 1-propylpentyl group, 2-propylpentyl group, and 3-propylpentyl group.
[0056] In group (I), R 2a1 , R 2a2 , R 2b1 , and R 2b2 is independently selected from -H, -F, and -CF; R 2a1 , R 2a2 , R 2b1 , and R 2b2 may be the same or different, but R 2a1 and R 2a2 At least one of them is -H and R 2b1 and R 2b2 At least one of the groups is -H. Therefore, R 2a1 , R2a2 , R 2b1 , and R 2b2 When -F or -CF3 is introduced, R 2a1 and R 2a2 Either one of and / or R 2b1 and R 2b2 It is introduced into one of the following.
[0057] In group (II), R 2a1 and R 2a2 is independently selected from -H, -F, and -CF; R 2a1 and R 2a2 may be the same or different, but R 2a1 and R 2a2 At least one of the groups is -H. Therefore, R 2a1 and R 2a2 When -F or -CF3 is introduced, R 2a1 and R 2a2 It is introduced into one of the following.
[0058] In formula (II), R 4 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8. 4 -C in n H 2n+1 , and -OC n H 2n+1 , and -SC n H 2n+1 -C n H 2n+1 is an alkyl group, the definition of which is as explained above.
[0059] In group (II), when Y is 1 or 2 and a thiophene ring is present, R 5 is introduced at the 3- or 4-position of the thiophene ring. 5 -H and -C n H 2n+1where n is an integer from 1 to 8. 5 -C in n H 2n+1 is an alkyl group, the definition of which is as explained above.
[0060] In groups (III), (IV) and (V), R D is preferably selected from the following groups (I'):
[0061] [ka]
[0062] Two R in groups (III), (IV), and (V) D That is, the groups (I') may be different or the same, but are preferably constituted as the same group.
[0063] In group (I'), each substituent is independently selected; R 1 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; and R 1 ´ and R 3 ' may be the same or different, but cannot be -H at the same time. 1 ´ and R 3 teeth 、 At least one of them is -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1is selected from.
[0064] R 1 ´ and R 3 -C in ´ n H 2n+1 is an alkyl group, which may be linear or branched. There is no particular restriction on the chain length as long as it is within the range of n=1 to 8. The definition of the alkyl group is as explained above.
[0065] In the group (I'), R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 R ' is independently selected from -H, -F, and -CF; 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 ' may be the same or different, but R 2a1 ´ and R 2a2 ´ is at least one of -H and R 2b1 ´ and R 2b2 ´ has at least one -H. Therefore, R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 When -F or -CF3 is introduced as R 2a1 ´ and R 2a2 ´ and / or R 2b1 ´ and R 2b2 ´ is introduced into either
[0066] As the D portion, preferably, it is a 4-(bis(4-alkoxyphenyl)amino)phenyl group, and more preferably, it is a 4-(bis(4-methoxyphenyl)amino)phenyl group. It is preferably a bis(4-alkoxyphenyl)amino group, and more preferably, it may be a bis(4-methoxyphenyl)amino group. It may also be preferably a tetrakis-4-alkoxyphenylcarbazole group, and more preferably, it is a tetrakis-4-methoxyphenylcarbazole group. Although not limited to these, it is particularly preferable to have such a tertiary amine group substituted with a phenyl group. In addition, the alkoxy group contained in the above group is preferably selected from an ethoxy group, a propoxy group, a butoxy group, and the like, in addition to a methoxy group.
[0067] The A portion has a substituent R A is introduced. Here, the substituent R A is preferably constituted as a 5-alkyl-2-thienyl group represented by the following group (VI): The wavy line in the group indicates the bonding position with the carbon-carbon double bond at the 9-position on the fluorene ring constituting the A moiety.
[0068] [ka]
[0069] In group (VI), R 6 -C m H 2m+1 The chain length is not particularly limited as long as it is in the range of m=6 to 16, and preferably in the range of m=8 to 12. m H 2m+1The group is an alkyl group, and the definition of the alkyl group is as explained above. For example, among the specific examples of the alkyl group explained above, in addition to the alkyl group having 6 to 8 carbon atoms, linear or branched nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, etc. can be mentioned. Preferable examples include an n-hexyl group, a 1, 2, 3, 4, or 5-methylhexyl group, a 1, 2, 3, or 4-ethylhexyl group, a 1, 2, or 3-propylhexyl group, a 1 or 2-butylhexyl group, and a 1-pentylhexyl group. 6 does not contain any heteroatom.
[0070] As the A portion, a substituent R A A 5-(2-ethylhexyl)-2-thienyl group has been introduced as the aryl group, but the present invention is not limited thereto.
[0071] [Preferable Examples of Hole Transport Material According to the Present Embodiment] A suitable example of the hole transport material according to this embodiment is a compound represented by the following general formula (2): Hereinafter, the hole transport material of general formula (2) may be referred to as "DHCF-17".
[0072] [ka]
[0073] The structure of DHCF-17, which is one of the preferred examples of the hole transport material according to this embodiment, will be described in detail. DHCF-17 has a DAD type structure. The A portion is configured as a fluorene ring. It is linked to the D portion at the 2-position and the 7-position on the fluorene ring. A 4-(bis(4-methoxyphenyl)amino)phenyl group is introduced into each D portion, and a 5-(2-ethylhexyl)-2-thienyl group is introduced into the 9-position on the fluorene ring via a carbon-carbon double bond.
[0074] [Method of synthesizing hole transport material according to this embodiment] The hole transport material according to the present embodiment can be easily synthesized by referring to the synthesis method described in the following Example 1. Note that Example 1 shows an example of a synthesis method for DHCF-17, which is a suitable example of the hole transport material according to the present embodiment, but the synthesis is not limited thereto, and other suitable methods can be used for synthesis.
[0075] A suitable example of the hole transport material according to this embodiment has a DAD type structure, and the A part has a fluorene ring consisting of carbon and hydrogen atoms. The A part has a substituent (preferably a 5-alkyl-2-thienyl group) introduced at the 9th position on the fluorene ring constituting the A part via a carbon-carbon double bond. Furthermore, the A part has a structure in which the D part is introduced at the 2nd and 7th positions on the fluorene ring of the A part. In the synthesis, the A part fluorene in which the 2nd and 7th positions at which the D part is introduced are substituted with halogen atoms such as Br, and a compound in which an aldehyde group is introduced at the position of introduction to the A part in the substituent desired to be introduced to the A part is reacted by Knoevenagel condensation reaction or the like to obtain an intermediate compound in which a desired substituent is introduced at the 9th position on the fluorene ring via a carbon-carbon double bond. Subsequently, the D part is introduced at the 2nd and 7th positions of the obtained intermediate compound by cross-coupling or the like known in the technical field, thereby synthesizing the hole transport material according to this embodiment. In the above-mentioned preferred example DHCF-17, a 4-(bis(4-methoxyphenyl)amino)phenyl group is introduced as the D part, and a 5-(2-ethylhexyl)-2-thienyl group is introduced into the A part via a carbon-carbon double bond. Specifically, as in Example 1 below, in synthesizing DHCF-17, first, an intermediate compound in which a substituent (5-(2-ethylhexyl)-2-thienyl group) is introduced into the fluorene ring constituting the A part via a double bond can be synthesized by a Knoevenagel condensation reaction between 2,7-dibromo-9H-fluorene and 5-(2-ethylhexyl)thiophene-2-carbaldehyde. Then, such an intermediate compound and 4-methoxy-N-(4-methoxyphenyl)-N-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)aniline are subjected to a Suzuki-Miyaura coupling reaction to synthesize DHCF-17. EXAMPLES
[0076] The present invention will now be described in detail with reference to the following examples.
[0077] Example 1 Preparation of hole transport material (DHCF-17) The hole transport material prepared in this example is called "DHCF-17" and is represented by the following general formula (2), and is a compound in which 4-(bis(4-methoxyphenyl)amino)phenyl groups are introduced as D moieties at the 2- and 7-positions of the fluorene ring constituting the A moiety, and a 5-(2-ethylhexyl)-2-thienyl group is introduced via a carbon-carbon double bond at the 9-position of the fluorene ring constituting the A moiety. The synthesis scheme will be explained based on Figure 5, which summarizes the synthesis scheme.
[0078] In the synthesis of DHCF-17, first, an intermediate compound (3) was synthesized by introducing a substituent into the fluorene ring constituting the A part through a double bond by the Knoevenagel condensation reaction of 2,7-dibromo-9H-fluorene (1) and 5-(2-ethylhexyl)thiophene-2-carbaldehyde (2). Next, DHCF-17 was synthesized by Suzuki-Miyaura coupling of intermediate compound (3) and 4-methoxy-N-(4-methoxyphenyl)-N-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)aniline (4), and purified by a standard method. The synthesis and purification of DHCF-17 are described in detail below.
[0079] (synthesis) [Step 1] Synthesis of intermediate compound (3) (db-Fluoro-TPA-EHT) In a 250 mL round bottom flask, 2,7-dibromo-9H-fluorene (1) (1.60 g, 4.9382 mmol), 5-(2-ethylhexyl)thiophene-2-carbaldehyde (2) (1.44 g, 6.4197 mmol), tetrabutylammonium bromide (TBAB) (0.56 g, 1.7283 mmol) and dry toluene (50 mL) were added. Then, 40% sodium hydroxide (NaOH) (50 mL) was added to the reaction mixture. The reaction mixture was heated at 70-80 °C for 18 hours under an argon atmosphere. After the reaction was completed, the reaction mixture was cooled and then poured into water and extracted with dichloromethane (hereinafter sometimes referred to as "DCM"). Then, it was washed with a brine solution, and the organic layer was concentrated under vacuum to obtain a crude product. The obtained crude product was purified by column chromatography (silica gel 100-200 mesh) using petroleum ether:DCM=1:4 as an eluent to obtain intermediate compound (3) (db-Fluoro-TPA-EHT) as a solid (yield: 1.60 g, 61%).
[0080] [Step 2] Synthesis of DHCF-17 The intermediate compound (3) (db-Fluoro-TPA-EHT) (0.30 g, 0.56 mmol) obtained in step 1, 4-methoxy-N-(4-methoxyphenyl)-N-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)aniline (4) (0.54 g, 1.2444 mmol) and potassium carbonate (K2CO3) (0.39 g, 2.83 mmol) were dissolved in dry toluene (14 mL) and water (7 mL). The reaction mixture was then degassed under an argon atmosphere for 30 minutes, and Pd(PPh3)4 (0.04 g, 0.034 mmol) was added. The reaction mixture was refluxed at 110°C for 18 to 20 hours under an argon atmosphere. The reaction mixture after the completion of the reaction was cooled to room temperature. The reaction mixture was then extracted with DCM, washed with water and brine solution, and the organic layer was then separated and concentrated to give the crude product of DHCF-17.
[0081] (Refining and Confirmation) The crude product obtained in step 2 was purified by column chromatography (silica gel 100-200 mesh) using n-hexane:DCM=3:7 as an eluent to obtain a pale orange solid DHCF-17 (yield: 0.30 g, yield: 54.15%). 1 The synthesis and purification of DHCF-17 were confirmed by H NMR analysis, mass spectrometry (hereinafter sometimes referred to as "Mass"), high performance liquid chromatography analysis (hereinafter sometimes referred to as "HPLC"), and ultraviolet-visible near-infrared spectroscopy analysis (hereinafter sometimes referred to as "UV-Vis"). 1 The results of the 1 H NMR analysis are shown in FIG. 7, the results of the mass analysis are shown in FIG. 8, and the results of the ultraviolet-visible-near infrared spectroscopic analysis are shown in FIG.
[0082] (Comparative Example 1) Preparation of DHCF-3 The hole transport material prepared as Comparative Example 3 is called "DHCF-3" represented by the following general formula (E), and is a compound described in Patent Document 1 (JP Patent Publication No. 2023-46046) described in the above [Background Art] section. In detail, DHCF-3 is a compound in which a 4-(bis(4-methoxyphenyl)amino)phenyl group is introduced as a D portion at each of the 2-position and 7-position on the fluorene ring constituting the A portion, and a 4-(bis(4-methoxyphenyl)amino)phenyl group, which is the same group as the D portion, is introduced at the 9-position on the fluorene ring constituting the A portion via a carbon-carbon double bond. The synthesis and purification can be performed based on the description of the above Patent Document 1, but will be briefly described below.
[0083] (synthesis) 2,7-Di(4-(bis(4-methoxyphenyl)amino)phenyl)-9H-fluorene (1) (0.01 g, 0.13 mmol), 4-(bis(4-methoxyphenyl)amino)benzaldehyde (2) (0.056 g, 0.17 mmol), TBAB (0.015 g, 0.45 mmol) and dry toluene (8 mL) were added to a 25 mL round bottom flask. Then, 40% sodium hydroxide (NaOH) (6 mL) was added. The reaction mixture was heated to reflux under argon atmosphere for 8 hours. After cooling, the reaction mixture was poured into water and extracted with DCM. It was then washed with brine solution and concentrated in vacuum to give the crude product.
[0084] (purification) The obtained crude product was purified by column chromatography (silica gel: 100-200 mesh) using petroleum ether:DCM=5:95 as an eluent 2-3 times to obtain a yellow solid DHCF-3 (yield: 0.10 g, 71.02%).
[0085] The structures of the hole transport materials synthesized in Example 1 and Comparative Example 1 are summarized below. [ka]
[0086] Example 2: Fabrication of solar cell 10 Hereinafter, a fabrication example of the solar cell 10 will be described as Example 2. The solar cell 10 can be fabricated with reference to known techniques such as those described in Chem. Mater., 2018, 30, 4193-4218, etc.
[0087] As an example, fluorine-doped tin oxide (FTO) glass (23 mm x 14 mm x 1.6 mm) was used for the transparent substrate 21. This FTO glass was laser scribed to form a recess 221 by removing the FTO, and was thoroughly washed. Next, a TiO2 dense film was formed as the blocking layer 3 by spray pyrolysis (SPD). Furthermore, a solution of commercially available TiO2 nanoparticle paste diluted with ethanol was dropped, applied by spin coating, and dried at 100°C. After drying, the substrate was baked at 450°C to form a TiO2 nanoparticle layer that would become the porous semiconductor 41. After baking, the substrate was cooled to room temperature.
[0088] Next, a perovskite precursor solution for forming the perovskite layer 44 was prepared. First, FAI (CH(NH2)2I) was weighed out, and a 1.7M PbI2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) solution prepared in advance was poured into it to prepare a FAPbI3 solution. Next, MAI (CH3NH3I) was weighed out, and a 1.7M PbBr2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) solution prepared in advance was poured into it to prepare a MAPbBr3 solution.
[0089] Finally, the FAPbI3 solution, the MAPbBr3 solution, and a previously prepared 1.7 M CsI / dimethyl sulfoxide (DMSO) solution were mixed to prepare a precursor solution to be subjected to spin coating.
[0090] The perovskite layer 44 was formed by dropping the above-mentioned precursor solution onto the TiO2 porous film and applying it by spin coating. After the application was completed, the film was heated at 100°C for 60 minutes and then cooled to room temperature.
[0091] Next, the hole transport layer 5 was prepared. As the hole transport material, DHCF-17 synthesized in the above Example 1 and DHCF-3 synthesized in the above Comparative Example 1 were used. Each hole transport material solution was weighed out so as to have a final concentration of 30 mM, and TPFB equivalent to 10% by weight was weighed out and added to the hole transport material. A mixture of the hole transport material and TPFB was dissolved in chlorobenzene to prepare a hole transport material solution. Note that cobalt complex (FK209), which is commonly used as a dopant, was not added. The hole transport layer 5 was formed by dropping the hole transport material solution onto the perovskite film and forming it by a spin coating method.
[0092] After the hole transport layer 5 was formed, a gold film of about 100 nm was formed by vacuum deposition, which was then removed to form the electrode 6, which was then laminated.
[0093] Example 3: Evaluation of cell performance of solar cell 10 In this example, an evaluation was performed on the cell performance of the solar cell 10. Here, the solar cell 10 using DHCF-17 synthesized in Example 1 above and DHCF-3 synthesized in Comparative Example 1 above as hole transport materials was examined.
[0094] The hole transport materials DHCF-17 (general formula (2)) of Example 1 and DHCF-3 (general formula (E)) of Comparative Example 1 examined in this example both have a DAD structure, and 4-(bis(4-methoxyphenyl)amino)phenyl groups are introduced as D moieties at the 2-position and 7-position on the fluorene ring of the A moiety. The A moieties are all configured as fluorene rings, but differ in the substituents introduced into the A moiety. In detail, in DHCF-17 of Example 1, a 5-(2-ethylhexyl)-2-thienyl group is introduced via a carbon-carbon double bond into the 9-position on the fluorene ring constituting the A moiety, whereas in DHCF-3 of Comparative Example 1, a 4-(bis(4-methoxyphenyl)amino)phenyl group identical to that of the D moiety is introduced via a carbon-carbon double bond into the 9-position on the fluorene ring constituting the A moiety.
[0095] Table 1 and Figure 9 show the results of the cell performance evaluation of solar cell 10. Table 1 summarizes the parameters of the short circuit current density (hereinafter sometimes referred to as "Jsc"), open circuit voltage (hereinafter sometimes referred to as "Voc"), fill factor (hereinafter sometimes referred to as "FF"), and conversion efficiency of solar cell 10. FF is the maximum output P at the point where the product of the current and voltage is maximum. max The conversion efficiency (PCE (%)) was calculated by dividing by (Voc × Jsc × FF ÷ incident light intensity).
[0096] [Table 1]
[0097] From the results in Table 1, the conversion efficiency of DHCF-17 in Example 1 was 21.0%, which was 20% or more, and showed higher solar cell characteristics than DHCF-3 in Comparative Example 1. It was found that the cell performance changed depending on the difference in the substituent introduced into the A part. In detail, it is considered that the difference in the substituent introduced into the A part caused a difference in the charge transfer characteristics within the molecule due to the electron-withdrawing property of the A part and the degree of steric interference between the substituent introduced into the A part and the D part, and as a result, the solar cell characteristics changed. In other words, in DHCF-17 in Example 1, the electron-withdrawing property of the A part was improved and the steric interference between the substituent introduced into the A part and the D part was eliminated, resulting in a larger push-pull effect within the molecule and improved charge transfer characteristics, which is considered to have improved the solar cell characteristics.
[0098] Furthermore, it is expected that the DHCF-17 of Example 1 has smooth intramolecular and intermolecular hole movement, which suppresses molecular oxidation and increases durability. Furthermore, since an alkyl group is introduced onto the fluorene ring constituting the A portion in DHCF-17, the DHCF-17 has good solubility in a solvent, and after dissolving DHCF-17 in an appropriate solvent, the hole transport layer 5 can be formed by a wet process such as a coating method by spin coating, which is advantageous in that the solar cell 10 can be easily fabricated.
[0099] It was also found that the addition of TPFB makes it possible to construct a highly durable solar cell 10. The addition of TPFB has the advantage that it can be carried out by a simple process of simply dissolving it in a solvent together with a hole transport material.
[0100] Example 4: Synthesis of various hole transport materials Hole transport materials were synthesized by modifying the group constituting the D portion of DHCF-17 in Example 1. The structures of the synthesized compounds are shown below. These compounds can be synthesized in step 2 of Example 1 above by modifying the compound coupled with the intermediate compound obtained in step 1 according to the structure of the D portion. [ka]
[0101] These compounds are also expected to have the same characteristics as DHCF-17. For example, when a solar cell 10 was produced for DHCF-41 in the same manner as in Examples 2 and 3 above and its cell performance was evaluated, it showed a photoelectric conversion efficiency equivalent to that of DHCF-3 as shown in Table 2 below and Figure 10, and exhibited excellent solar cell characteristics.
[0102] [Table 2]
[0103] In the above-described embodiment, the following configurations are envisaged. (1) A hole transport material having a donor-acceptor-donor (DAD) structure represented by the following general formula (1): [ka] [In general formula (1), The two D regions are regions having the same structure, Each D moiety has a structure selected from the following groups (I), (II), (III), (IV), and (V): [ka] (In group (I), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 , R 2a2 , R 2b1 , and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H and R 2b1 and R 2b2 At least one of them is -H.) [ka] (In group (II), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1, and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 and R 2a2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H, R 4 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; Y is 1 or 2, and R 5 If exists, R 5 is introduced at the 3- or 4-position of the thiophene ring in group (II), -H and -C n H 2n+1 where n is an integer of 1 to 8. [ka] [ka] [ka] (In group (III), group (IV), and group (V), X and Y are each independently an integer of 0, 1, or 2; The Two R's D each independently has a structure represented by the following group (I'), [ka] (In the group (I´), X' and Y' are each independently an integer of 0, 1, or 2. R 1´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 ´ and R 3 ´ is not simultaneously -H, R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 ´ and R 2a2 ´ is at least one of -H and R 2b1 ´ and R 2b2 ´ At least one of them is -H. )) In general formula (1), R A has a structure represented by the following group (VI): [ka] (In group (VI), R 6 -C m H 2m+1 where m is an integer between 6 and 16.
[0104] The hole transport material according to this embodiment has excellent hole transport properties that can capture and move holes stably and efficiently. In detail, the hole transport material according to this embodiment has a DAD type structure, and the A part is configured to include an electron-accepting group such as a fluorene ring composed of carbon atoms and hydrogen atoms, and the D part is introduced to the 2-position and the 7-position on the fluorene ring, respectively, and further, a 5-alkyl-2-thienyl group is introduced to the 9-position on the fluorene ring via a carbon-carbon double bond. By configuring in this way, the electron-withdrawing property of the A part is improved, and the steric interference between the substituent of the A part and the D part is eliminated, so that the push-pull effect in the molecule of the hole transport material is increased and the charge transfer property in the molecule is improved. As a result, the transfer of electrons in the molecule is smooth and the charge separation of HOMO-LUMO is more clear. That is, in the hole transport material according to this embodiment, electrons are concentrated in the D part at the HOMO and HOMO-1 levels, and electrons are concentrated in the A part at the LUMO level. In this way, the hole transport material of this configuration can exhibit excellent hole transport properties due to the improved charge transfer properties within the molecule. Furthermore, by using a fluorene ring that does not contain a heteroatom in the A portion, the inhibition of electron-withdrawing properties caused by the lone pair of the heteroatom, which occurs in LD29 and the like described in the [Prior Art] section, is eliminated, and the hole transport material can function more effectively.
[0105] In addition, since the hole transport material according to this embodiment has a deep HOMO energy level, the arrangement with the HOMO level of the perovskite can be appropriately adjusted, and therefore, the hole transport properties can be improved, and further, there is an advantage that the solar cell efficiency can be easily improved.
[0106] The hole transport material according to this embodiment exhibits almost no light absorption in the visible light region, and its light absorption intensity in the region of up to 450 nm is weaker than that of the general-purpose spiro-OMeTAD described in the prior art section. Therefore, the solar cell 10 using the hole transport material according to this embodiment can minimize the light absorption loss caused by the hole transport material, and can be expected to have high photoelectric conversion efficiency.
[0107] The hole transport material according to the present embodiment also has excellent properties in terms of solubility in a solvent. In particular, the solubility in a solvent is improved by introducing a 5-alkyl-2-thienyl group having a long-chain alkyl group as the A portion. Therefore, the workability when manufacturing the solar cell 10 is improved, and a wet process such as a coating method by spin coating can also be used, making it easy to form the hole transport layer 5 of the solar cell 10. In addition, since the hole transport material according to the present embodiment is soluble in a non-polar solvent, it is possible to form the hole transport layer 5 of the solar cell 10 using a solvent that is inexpensive and has a low environmental impact. On the other hand, when manufacturing the hole transport layer 5, spiro-OMeTAD, which has been widely used in the past, generally uses chlorobenzene as a solvent. However, chlorobenzene contains chlorine in the molecule and is expensive, so that the cost of equipment including post-processing such as solvent disposal is high, and there are problems such as a large load on safety and the environment due to exhaust gas leakage.
[0108] In addition, the hole transport material according to the present embodiment can be synthesized in a short time with fewer synthesis steps using inexpensive raw materials, and a high purity product can be provided through a simple purification step. Therefore, it is possible to reduce the costs required for synthesis and purification without requiring expensive reagents or complicated steps, and it is possible to provide an inexpensive, high-performance hole transport material.
[0109] Furthermore, due to the hydrophobic effect of the long-chain alkyl group of the 5-alkyl-2-thienyl group introduced into the A portion, the water resistance of the solar cell 10 incorporating the hole transport material of this embodiment is improved, and the durability of the solar cell 10 can be expected to be improved.
[0110] As described above, the hole transport material according to this embodiment has excellent properties and can be suitably used as a hole transport material for the solar cell 10.
[0111] (2) In the hole transport material of (1), R A is preferably 5-(2-ethylhexyl)-2-thienyl.
[0112] In the hole transport material according to this embodiment, the group introduced into the A moiety via a carbon-carbon double bond is a 5-(2-ethylhexyl)-2-thienyl group, which further improves the electron-withdrawing ability of the A moiety and more effectively suppresses the steric interference between the substituent of the A moiety and the D moiety, thereby enabling the push-pull effect within the molecule of the hole transport material to be appropriately controlled and the charge transfer properties within the molecule to be further improved. This makes it possible to provide a hole transport material having excellent hole transport properties, in particular, capable of stably and efficiently capturing and transferring holes.
[0113] In the hole transport material of (3)(1), it is preferable that it is represented by the following general formula (2) or general formula (5). [ka] [ka]
[0114] In the hole transport material according to this embodiment, a 4-(bis(4-methoxyphenyl)amino)phenyl group or a bis(4-methoxyphenyl)amino group is introduced into the D moiety, and a 5-(2-ethylhexyl)-2-thienyl group is introduced into the A moiety via a carbon-carbon double bond. This further improves the electron-withdrawing ability of the A moiety and more effectively suppresses the steric interference between the substituent of the A moiety and the D moiety, thereby enabling the push-pull effect within the molecule of the hole transport material to be appropriately controlled and the charge transfer properties within the molecule to be further improved. This makes it possible to provide a hole transport material having excellent hole transport properties, in particular capable of stably and efficiently capturing and transferring holes.
[0115] (4) A solar cell 10 using the hole transport material of (1), comprising: a substrate 2 having a transparent conductive film 22; a blocking layer 3 that delivers electrons to the transparent conductive film 22 and prevents reverse electron transfer; a power generation layer 4 formed by stacking a perovskite layer 44 that is excited by light to generate the electrons on a porous semiconductor 41; and a hole transport layer 5 through which holes generated from the perovskite layer 44 pass and which contains the hole transport material, stacked in this order as a laminate 11; and an electrode 6 composed of a photoelectrode 61 that emits the electrons via the transparent conductive film 22 and a counter electrode 62 provided on the surface of the hole transport layer 5.
[0116] The solar cell 10 according to this embodiment includes a hole transport layer 5 formed using the hole transport material according to this embodiment having excellent properties as described above. In particular, the hole transport material according to this embodiment has excellent hole transport properties that can capture and move holes stably and efficiently. In particular, the hole transport material according to this embodiment has a large push-pull effect in its molecule, exhibits excellent intramolecular charge transfer properties, and can exhibit excellent hole transport properties. In addition, as described above, the hole transport material according to this embodiment has excellent light absorption properties and also has excellent properties in terms of durability. Therefore, the solar cell 10 according to this embodiment uses a hole transport material having excellent properties as the hole transport layer 5, thereby improving the photoelectric conversion efficiency, thereby improving the cell performance, and further improving the durability of the solar cell 10.
[0117] In addition, when conventional spiro-OMeTAD and LD29, etc., described in the above [Prior Art] section, are used as hole transport materials, LiTFSI is generally added as a dopant having a function of improving hole transport efficiency. However, there are problems in terms of durability, such as the lithium ions contained in LiTFSI diffusing out of the hole transport layer 5 and the solar cell efficiency decreasing over time due to the strong hygroscopicity of LiTFSI itself. In the solar cell 10 of the present configuration, the durability of the solar cell 10 can be improved by adding TPFB instead of LiTFSI. This is thought to be because the molecular size of the cation part of TPFB is large, making it difficult to diffuse, and TPFB itself is not hygroscopic.
[0118] Furthermore, as described above, the hole transport material according to the present embodiment does not require expensive reagents or complicated processes and can be synthesized inexpensively and simply. By using the hole transport material according to the present embodiment, which is thus cost-effective, it is possible to reduce the price of the solar cell 10 according to the present embodiment.
[0119] [Other embodiments] In the above embodiment, a perovskite solar cell 10 is shown as an example of the solar cell 10 using the hole transport material according to this embodiment, but this hole transport material may also be used in devices using OPV (organic thin-film solar cell), organic electroluminescence (EL), organic semiconductors, and the like. [Industrial Applicability]
[0120] The present invention can be used as a hole transport material for use in perovskite solar cells 10 and the like that include a perovskite compound formed from an organic and inorganic hybrid compound. [Explanation of symbols]
[0121] 2. Board 3 Blocking Layer 4 Power generation layer 5. Hole transport layer 6 electrodes 10. Solar Cells 11 Laminate 21 Transparent substrate 22 Transparent conductive film 41 Porous Semiconductors 44 Perovskite layer 61 Photoelectrode 62 Counter electrode
Claims
1. A hole transport material having a donor-acceptor-donor (DAD) structure represented by the following general formula (1): 【Chemistry 1】 [In general formula (1), The two D regions are regions having the same structure, Each D moiety has a structure selected from the following groups (I), (II), (III), (IV), and (V): 【Chemistry 2】 (In group (I), X and Y are each independently an integer of 0, 1, or 2. R 1 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; R 3 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 is not simultaneously -H, R 2a1 , R 2a2 , R 2b1 , and R 2b2 are each independently -H, -F, or -CF 3 where R 2a1 and R 2a2 At least one of R is -H, 2b1 and R 2b2 At least one of is -H.) 【Chemistry 3】 (In group (II), X and Y are each independently an integer of 0, 1, or 2. R 1 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; R 3 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 is not simultaneously -H, R 2a1 and R 2a2 are each independently -H, -F, or -CF 3 where R 2a1 and R 2a2 At least one of is -H, R 4 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n is an integer from 1 to 8; Y is 1 or 2, and R 5 If present, R 5 is introduced at the 3- or 4-position of the thiophene ring in group (II), and -H and -C n H 2n+1 where n is an integer from 1 to 8. 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 (In group (III), group (IV), and group (V), X and Y are each independently an integer of 0, 1, or 2; Two R's D each independently has a structure represented by the following group (I'): 【Chemistry 7】 (In the group (I'), X' and Y' are each independently an integer of 0, 1, or 2. R 1 ´ is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; However, R 1 ´ and R 3 ´ is not simultaneously -H, R 2a1 ', R 2a2 ', R 2b1 ', and R 2b2 ' are each independently -H, -F, or -CF 3 where R 2a1 ´ and R 2a2 At least one of R′ is —H, 2b1 ´ and R 2b2 ' At least one of them is -H.) In general formula (1), R A has a structure represented by the following group (VI): 【Chemistry 8】 (In group (VI), R 6 is -C m H 2m+1 where m is an integer from 6 to 16.
2. R A 2. The hole transport material of claim 1, wherein is 5-(2-ethylhexyl)-2-thienyl.
3. The hole transport material according to claim 1 , represented by the following general formula (2) or general formula (5): 【Chemistry 9】 【Chemistry 10】
4. A solar cell using the hole transport material according to any one of claims 1 to 3, A substrate having a transparent conductive film; a blocking layer that transfers electrons to the transparent conductive film and prevents reverse electron transfer; a power generation layer formed by laminating a perovskite layer, which is excited by light to generate the electrons, on a porous semiconductor; a hole transport layer through which holes generated from the perovskite layer pass and which has the hole transport material; and a photoelectrode that emits the electrons through the transparent conductive film, and an electrode that is composed of a counter electrode provided on a surface of the hole transport layer.
Citation Information
Patent Citations
Hole transport material and solar cell employing hole transport material
JP2023046046A
